Determination of the power density distribution in a PWR reactor based on neutron flux measurements at fixed reactor incore detectors. (April 2016) - Dias, A.M.; Silva, F.C.
Highlights: A method to determine linear power density distribution is presented. Tests are performed in a commercial PWR reactor. Neutron flux measurements are made in the internal core detectors. The neutron fluxes are mapped with the aeroball system. The results were compared with those mapped neutron fluxes. Abstract: The proportionality between the neutron flux signal and the power density allows the determination of the linear power density at the detector location. Applying this property, it is shown in this paper the evolution of the power density monitoring methods, using neutron flux measurements in commercial reactors of the PWR type. For these measurements detectors positioned externally and internally to the reactor pressure vessel are used. As main task, this paper presents a calculation method that aims to determine the linear power density distribution in a PWR, in 3D, based on the measurements at fixed neutron detector positions in the reactor core. The power densities measured at the detectors locations in the reactor core, are used to correct the power densities, which were calculated from design data. Accordingly, the neutron flux is corrected for all other regions of the reactor core and a new power density distribution is determined. To evaluate the obtained power distribution, this procedure was applied for the beginning of cycle-1 of a commercial PWR of 3765 MWth. This calculated power distribution was compared to the power distribution measured using the neutron flux mapping performed with the aeroball system, which consists of indirect measurements of the neutron flux through probe activation in axial and radial positions of the reactor core. The observed differences resulted in a standard deviation of less than 3% and a maximum deviation less than 5%.